Synthesis And Biological Studies Of 1, 2, 3, 4-Tetrahydro-6-Methyl- 2-Oxopyrimidine-5-Carboxamide Derivative - PARTHIV KANTILAL CHAUDHARI, (International Journal of Pharma and Bio Sciences, 2012)
From various biomedical applications and pharmacological profile of pyrimidine derivative, the novel series of 1, 2, 3, 4-tetrahydro-6-methyl- 2-oxopyrimidine-5-carboxamide derivative (PK-101 to PK-110) are synthesized. The synthesis of these thirty compounds was achieved by the Biginelli reaction of acetoacetanilide, urea derivatives and corresponding aldehydes. The reaction is catalysed by concentrated hydrochloric acid (HCl). The products were characterized by various analytical techniques like FT-IR spectroscopy, mass spectrometry, 1H NMR spectroscopy and elemental analysis. The newly synthesized compounds were subjected to various biological activities viz., antimicrobial, antimycobacterial.